Facing Racism and Sexism in Science by Fighting Against Social Implicit Bias: A Latina and Black Woman’s Perspective - Calaza, Karin C.; Erthal, Fátima C. S.; Pereira, Mirtes G.; Macario, Kita C. D.; Daflon, Verônica T.; David, Isabel P. A.; Castro, Helena C.; Vargas, Maria D.; Martins, Laura B.; Stariolo, Jasmin B.; Volchan, Eliane; de Oliveira, Leticia (Frontiers in Psychology, 2021)
The editors of several major journals have recently asserted the importance of combating racism and sexism in science. This is especially relevant now, as the COVID-19 pandemic may have led to a widening of the gender and racial/ethnicity gaps. Implicit bias is a crucial component in this fight. Negative stereotypes that are socially constructed in a given culture are frequently associated with implicit bias (which is unconscious or not perceived). In the present article, we point to scientific evidence that shows the presence of implicit bias in the academic community, which contributes to strongly damaging unconscious evaluations and judgments of individuals or groups. Additionally, we suggest several actions aimed at (1) editors and reviewers of scientific journals, (2) people in positions of power within funding agencies and research institutions and (3) members of selection committees to mitigate this effect. These recommendations are based on the experience of a group of Latin American scientists comprising Black and Latin women, teachers and undergraduate students who participate in a women in science working group at universities in the state of Rio de Janeiro, Brazil. With this article, we hope to contribute to reflections, actions and the development of institutional policies that enable and consolidate diversity in science and reduce disparities based on gender and race/ethnicity.